Households' ICT access and educational vulnerability of children in Ghana - Karakara, Alhassan Abdul-Wakeel,Osabuohien, Evans (African Governance and Development Institute, 2019)
Education is said to be a basic human right, and central to unlocking human capabilities. However, Sub-Sahara Africa (SSA) has the highest number of children out of school and learning disadvantages. Most studies on child vulnerability concentrate on disaster, disability and HIV effects on children. Thus, this study investigates the likelihood of a child being educationally disadvantaged or risk school dropout. Ghana Demographic and Health Survey (GDHS) data for 2014 with binary and multinomial logistic regressions are used to determine the likelihood of a child being educationally disadvantaged. The findings reveal disparity in wealth distribution in Ghana. Wealth of family is a determinant of child success in education and urban household children are less likely to be disadvantaged in learning outcomes. Households' access to ICTs enhances child learning at home and; hence, reduces the risk of a child being educationally disadvantaged. Policy implications and suggestions for further studies are discussed in the paper.
10419/227975
Keywords: Graue Literatur; Child educational disadvantage; Ghana; Households; ICTs; Wealth disparity